Design and Development of Sustainable Lean Manufacturing Using Interpretive Structural Model (ISM) Approach: Examining the Factors for Successful Implementation of Sustainable Lean Manufacturing (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In the recent time many industries are implementing lean manufacturing to reduceeliminating wastes. But, while implementing LM in the industries the faces many issues. In this research workers involvements, communication and improved material handling and housekeeping are the three factors which have high driving power and low dependent power. So work on these issues can lean to successful implementation of the lean manufacturing for the sustainable development.Waste minimization and improving efficiency have been identified as key objectives of lean manufacturing system implementation. Literature review and subsequent discussions with experts have helped to sort the factor relevant to lean manufacturing system implementation based upon their importance. Questionnaire based survey has been carried out to rank these identified factor followed by structural modeling. Top management commitment has been ranked the most important factor as a result of survey analysis and also has been identified as the most important bottom level factor in ISM hierarchy. MICMAC analysis has been utilized to classify the factors.